Fuzzy control of continuous stirred tank reactor (CSTR) - Mohd Noor, Samsul Bahari; Marhaban, Mohammad Hamiruce; Mansor, Hasmah (2005)
Continuous Stirred Tank Reactor (CSTR) involves complex reactions, highly non-linear and very hard to control by conventional methods. Fuzzy controller is introduced in this research to control the CSTR. A powerful design and simulation tool which is MATLAB and SIMULINK has been used for evaluation and test. The main objective of this research is to build fuzzy controller for the CSTR that are capable to work in high state of sensitivity as well as being able to response fast towards any inputs using Mamdani and Sugeno inference mechanisms. The performances of two fuzzy controllers are then compared. The results show that the overall performance of both Mamdani and Sugeno based fuzzy controller are excellent. Sugeno based fuzzy controller has improved the response time of Mamdani based fuzzy controller and reduced the steady state error. Furthermore, the simulation time is also reduced. The outstanding achievement in this research is the fuzzy controller is very robust towards extremely high step change in inlet temperature.